2022
DOI: 10.31620/jccc.06.22/16
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Brand Awareness on Enrollment Decision Process Moderated by Students Gender for Hei

Abstract: The increasing competition in higher education institutions has made brand awareness an integral part of their marketing activity, to increase the student enrollment rate. The study investigates the factors of brand awareness and its relationship with each stage of a student’s enrolment decision process, keeping the student’s gender as a moderator. Primary and secondary sources were used to do the research. A structured questionnaire was framed and data was collected from 1000 students from management colleges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In Table 6, it is known that the coefficient value is 0.638 the t-statistic value is 6,517 > 1.96 and the p-value is 0.000 < 0.05, there is an influence of brand awareness on the purchase decision of Mixue products in UBP Karawang Management students. This is supported by previous research conducted by [20]- [22] that in the decision-making process, brand awareness plays an important role because brand awareness can influence the purchase decision of a product/service. Brand awareness affects the process of taking consumers when choosing tourist attractions to visit.…”
Section: Figure 2 Research Results Modelsupporting
confidence: 71%
“…In Table 6, it is known that the coefficient value is 0.638 the t-statistic value is 6,517 > 1.96 and the p-value is 0.000 < 0.05, there is an influence of brand awareness on the purchase decision of Mixue products in UBP Karawang Management students. This is supported by previous research conducted by [20]- [22] that in the decision-making process, brand awareness plays an important role because brand awareness can influence the purchase decision of a product/service. Brand awareness affects the process of taking consumers when choosing tourist attractions to visit.…”
Section: Figure 2 Research Results Modelsupporting
confidence: 71%
“…Perhaps since women place more emphasis on brand emotional resonance, while men place more emphasis on the practicality of brand information, it affects the speed of social media brand information dissemination among students of different genders. Bohara & Panwar (2022) studied that the increasingly fierce competition in higher education institutions has made brand awareness an indispensable part of marketing activities to increase student enrollment rates. The research results indicate that the factors that determine brand awareness have been identified.…”
Section: The Moderating Role Of Gender In the Impact Of Student Socia...mentioning
confidence: 99%
“…While recent studies have examined university branding from the perspective of multiple stakeholders (Amani, 2022;Balmer & Wang, 2016), limited attention has been given to students' viewpoints. Furthermore, many of these studies focus on specific aspects, such as brand identity (Bohara & Panwar, 2022), brand image (Panda et al, 2019;Sultan & Wong, 2019), or brand equity (Pinar et al, 2020;Stukalina & Pavlyuk, 2021). Current research needs to comprehensively address the dimensions, metrics, and components of university branding (Jois & Chakrabarti, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Methodologically, research in this domain often employs structural equation modeling (Bohara & Panwar, 2022;Dennis et al, 2016;Kango et al, 2021), qualitative analysis (Clark et al, 2020;Hall & Witek, 2016), or regression analysis (Jez, 2014;Kawpong & Walee, 2020). However, additional studies are needed to combine the Delphi method with the analytic hierarchy process (AHP).…”
Section: Introductionmentioning
confidence: 99%